Recovery timeline following resistance training in professional female soccer players. Issue 3 (2nd July 2020) - Goulart, Karine Naves de Oliveira; Duffield, Rob; Junior, Geraldo Oliveira Carvalho; Passos Ramos, Guilherme; Pimenta, Eduardo Mendonça; Couto, Bruno Pena
ABSTRACT: Objective: Determine the time-course of recovery after a resistance training session (RT) in female soccer players. Methods: Ten Brazilian female professional soccer players undertook testing prior to and at immediately, 24 and 48 h post-RT. RT was a high-speed and low-load session, consisting of three sets of six repetitions of lower body exercises at 50%1RM. Tests included countermovement jump (CMJ) and 20 m sprint, with the best and mean efforts recorded. Delayed onset muscle soreness (DOMS), total quality recovery (TQR) and Brazilian Mood Scale (BRAMS) were collected. Repeated measures ANOVA with effect sizes (ES) assessed the time-course of recovery (α=0.05). Results: Mean and best CMJ performance decreased immediately post-RT (p<0.05, ES=−0.49; −0.65, respectively), though no significant differences and trivial-small effects existed at 24h (p>0.05, ES=−0.15; −0.08) and 48h (p>0.05, ES=0.14; −0.21). No significant differences and trivial-small effects were evident at any time for mean or best 10m (p>0.05, ES=−0.18–0.26) or 20m (p>0.05, ES=−0.08–0.19) performance. DOMS, TQR, fatigue and vigor did not change following RT (p>0.05; ES=-0.51-0.48). Conclusion: Light-load, high-speed RT induces only small, immediate changes in CMJ, without prolonged suppression of recovery parameters. Such training seems feasible for inclusion in competitive micro-cycles at least 24h prior to the next match.